PENERAPAN SISTEM INFORMASI PELAYANAN PERIZINAN TERPADU (SIPINTER) DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN TANGERANG - Nur Annisaa; Riny Handayani (JCI Publisher, 2026)
Abstract This study aims to analyze the implementation of the Integrated Licensing Service Information System (SIPINTER) at the Investment and One-Stop Integrated Services Office (DPMPTSP) of Tangerang Regency. The research is grounded in issues of low institutional responsiveness in following up on complaints, mismatches between actual service completion time and the Standard Operating Procedure (SOP), and uneven public socialization of the system. This study employs a descriptive method with a qualitative approach, using 3-dimensional e-government success model, namely Support, Capacity, and Value, as the analytical framework. Data were collected through field observation, regulatory documentation review, and in-depth interviews. The findings indicate that the Support dimension is backed by strong political will, allocated funding, and multi-channel socialization that has driven growth in registered users, though technical assistance responsiveness outside office hours remains weak. The Capacity dimension shows adequate human resources and staff competence, but the technological infrastructure remains prone to disruptions such as OTP delivery failures and server downtime. The Value dimension has produced tangible benefits in efficiency and service transparency, yet this value is undermined by document processing delays exceeding SOP standards, driven by a